DEVELOPING STUDENTS' SPEECH COMPETENCE THROUGH INTERACTIVE METHODS IN PRIMARY SCHOOL MOTHER TONGUE LESSONS - Olimjonova Dilnavoz Maribjon qizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the methodological foundations of developing speech competence among primary school pupils through interactive teaching methods in Mother Tongue lessons. The study was conducted with 21 third-grade pupils of Innovation Erudit School in Andijan. Based on pedagogical observation, practical activities, and comparative analysis, the effectiveness of interactive methods in improving pupils' oral and written speech, vocabulary, independent thinking, and communication skills was identified. The findings indicate that the systematic use of interactive teaching methods is an effective pedagogical approach to developing speech competence in primary education.